Efficient DNA Repair Mitigates Replication Stress Resulting in Less Immunogenic Cytosolic DNA in Radioresistant Breast Cancer Stem Cells - Meyer, Felix; Engel, Anna Maria; Krause, Ann Kristin; Wagner, Tim; Poole, Lena; Dubrovska, Anna; Peitzsch, Claudia; Rothkamm, Kai; Petersen, Cordula; Borgmann, Kerstin (Frontiers in Immunology, 2022)
Cancer stem cells (CSCs) are a major cause of tumor therapy failure. This is mainly attributed to increased DNA repair capacity and immune escape. Recent studies have shown that functional DNA repair via homologous recombination (HR) prevents radiation-induced accumulation of DNA in the cytoplasm, thereby inhibiting the intracellular immune response. However, it is unclear whether CSCs can suppress radiation-induced cytoplasmic dsDNA formation. Here, we show that the increased radioresistance of ALDH1-positive breast cancer stem cells (BCSCs) in S phase is mediated by both enhanced DNA double-strand break repair and improved replication fork protection due to HR. Both HR-mediated processes lead to suppression of radiation-induced replication stress and consequently reduction of cytoplasmic dsDNA. The amount of cytoplasmic dsDNA correlated significantly with BCSC content (p=0.0002). This clearly indicates that HR-dependent avoidance of radiation-induced replication stress mediates radioresistance and contributes to its immune evasion. Consistent with this, enhancement of replication stress by inhibition of ataxia telangiectasia and RAD3 related (ATR) resulted in significant radiosensitization (SER37 increase 1.7-2.8 Gy, p<0.0001). Therefore, disruption of HR-mediated processes, particularly in replication, opens a CSC-specific radiosensitization option by enhancing their intracellular immune response.